Oral Administration of Aloe vera Ameliorates Wound Healing through Improved Angiogenesis and chemotaxis in Sprague Dawley Rats - Ali, Fatima; Wajid, Nadia; Sarwar, Maryam G.; Qazi, Aamer M. (Current Pharmaceutical Biotechnology, 2021)
Background: Aloe vera has been reported as a topical antibiotic and healing agent for wounds, but advantages of oral administration and mechanisms of wound healing have not been reported. Present study focuses on the evaluation of effects of oral administration of Aloe vera for excisional cutaneous wounds in Sprague Dawley rats. Methods: Sprague Dawley (SD) rats were inflicted with excisional wounds and were either treated with Aloe vera orally (Aloe vera) or kept untreated (wound). In contrast, healthy rats were kept as control group. Wound area was measured from day 7th to day 21st. Collagen content was estimated by hydroxyproline assay. Histology was analysed by hematoxylin and eosin staining. Angiogenesis was observed by indirect ELISA for Insulin like Growth Factor (IGF-1) and Vascular Endothelial Growth Factor (VEGF) protein from skin, serum and bone marrow. Chemotaxis was evaluated by RT-PCR analysis for Stromal cell-Derived Factor-1 (SDF-1) and C-X-C chemokine receptor type 4 (CXCR-4) from skin and bone marrow. Results: Aloe vera healed wounds earlier than untreated rats with gradual improvement in wound areas and collagen content. Aloe vera also improved the expression of IGF-1 and VEGF in skin and bone marrow indicating an improvement in angiogenesis. RT- PCR analysis showed increased expression of genes for chemotaxis (SDF-1 and CXCR-4) in skin and bone marrow. Conclusion: Aloe vera improves healing by increasing collagen content, improving angiogenesis and chemotaxis.
Keywords: Wounds